Measurement of Quality of Life in Outpatient Hypertension Patients Utilizing the EQ-5D-5L Method at a Hospital in Bandung - Oskar Skarayadi; Muhammad Didit Prasodjo; Afifah B Sutjiatmo (Institute Of Computer Science (IOCS), 2023)
The prevalence rate of hypertension continues to increase every year. Strategies are needed to help health professionals and the public discover the tendency of hypertension as early as possible. Measuring quality of life is one way to discover the description of the patient's condition. It can help health workers and the public prevent and treat hypertension. One of the questionnaires to assess the quality of life is the European Quality of Life - 5 Dimensions- 5 Level (EQ-5D-5L) form issued by EuroQol. This questionnaire consists of questions and a visual analog scale (VAS). The research was conducted on August 27, 2018 - September 14, 2018. Using the EQ-5D-5L questionnaire, the self-care aspect (SC) is the dimension that is least affected by the patient's hypertension, with a percentage of 6%. The pain or discomfort dimension (PD) is the most affected, with a percentage of 54%, where 12 people (36%) do not have problematic dimensions, so the index value is 1. Measurements with VAS show that most patients have a VAS value of 90 55. % with an average value of 70.